Modern state of preschool education in different parts of Ukraine - Олеся Корнус; Анатолій Корнус; Микита Коновалов; Олена Король; Ольга Скиба (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2022)
The role of social factors has increased significantly in modern society. Education is essential for raising the intellectual and cultural level of inhabitants in any country. The purpose of this article is to analyze modern state of preschool education in different parts of Ukraine and to point at regional disparities in accessibility of preschool education services. This article gives analysis to modern state of preschool education in different parts of Ukraine. Research was based on several indicators such as number of children involved in preschool education, number of preschools in different regions of Ukraine, preschool enrollment rates and number of children actually attending preschools per 100 available places. Level of development of preschool education in cities and rural areas has been studied in regional context of Ukraine. It was also calculated social density of preschools and indexes of both territorial concentration and localization of preschools in the country. Social density of preschools was also analyzed in the study.